Monocyte and myeloid dendritic cell activation occurs throughout HIV type 2 infection, an attenuated form of HIV disease. - Cavaleiro, R. (2015)
© The Author 2013. Published by Oxford University Press on behalf of the Infectious Diseases Society of America. All rights reserved.